Analysis Of The 7P Marketing Mix At Panorama Hejo, Sentul - Rezki Orientani; Anisa Zahwa Akbara (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
Tourism from 2021 to 2023 has continued to show growth in West Java, particularly in the Bogor Regency/City area. The increasing competition in the tourism industry demands that stakeholders be able to compete by focusing on the marketing mix. Panorama Hejo is a new nature tourism attraction and accommodation in the Sentul area, established in 2023. The urgency of this research to help identify the overall 7Ps and how to develop them to make the destination more attractive to tourists. This is particularly relevant due to several complaints found in Google Reviews from tourists who have previously visited Panorama Hejo in Bogor. Therefore, this study is expected to identify the 7Ps marketing mix according to both stakeholders and tourists, assess the potential for development, and provide recommendations for improvement for Panorama Hejo. The research was conducted through field observations and interviews with stakeholders and tourists who were able to provide information regarding the marketing mix of Panorama Hejo.